Arp2/3 complex inhibition prevents meiotic maturation in porcine oocytes. - Fei Wang; Ga-Young An; Yu Zhang; Hong-Lin Liu; Xiang-Shun Cui; Nam-Hyung Kim; Shao-Chen Sun (PLoS ONE, 2014)
The Arp2/3 complex regulates actin nucleation, which is critical for a wide range of cellular processes, such as cell polarity, cell locomotion, and endocytosis. In the present study, we investigated the possible roles of the Arp2/3 complex in porcine oocytes during meiotic maturation. Immunofluorescent staining showed the Arp2/3 complex to localize mainly to the cortex of porcine oocytes, colocalizing with actin. Treatment with an Arp2/3 complex specific inhibitor, CK666, resulted in a decrease in Arp2/3 complex localization at the oocyte cortex. The maturation rate of porcine oocytes decreased significantly after CK666 treatment, concomitant with the failure of cumulus cell expansion and oocyte polar body extrusion. The fluorescence intensity of F-actin decreased in the cytoplasm, and CK666 also disrupted actin cap formation. In summary, our results illustrate that the Arp2/3 complex is required for the meiotic maturation of porcine oocytes and that actin nucleation is critical for meiotic maturation.